Ulcerative Colitis as a Novel Cause of Increased Need for Levothyroxine - Virili, Camilla; Stramazzo, Ilaria; Santaguida, Maria Giulia; Bruno, Giovanni; Brusca, Nunzia; Capriello, Silvia; Cellini, Miriam; Severi, Carola; Gargano, Lucilla; Centanni, Marco (Frontiers in Endocrinology, 2019)
Background: Thyroxine absorption takes place at small intestine level and several disorders affecting this intestinal tract lead to thyroxine malabsorption. An increased need for thyroxine was also observed in gastric disorders due to the variations in drug dissolution and/or in its ionization status. Ulcerative colitis (UC) is an inflammatory bowel disease that has been postulated as potential cause of increased need for thyroxine but there is a lack of evidence on this topic. This study was aimed at measuring the thyroxine requirement in hypothyroid patients bearing UC. Patients and Methods: Among 8573 patients with thyroid disorders consecutively seen in our referral center from 2010 to 2017, we found 34 patients with a definite diagnosis of UC. Thirteen of them were hypothyroid (12 F/1 M; median age=53 years), bearing UC during the remission phase and in need for thyroxine treatment thus representing the study group. The dose of T4 required by UC patients has been compared to the one observed in 51 similarly treated age- and weight-matched patients, compliant with treatment and clearly devoid from any gastrointestinal and /or pharmacological interference. Results: To reach the target serum TSH, the dose of thyroxine owed to be increased in twelve out of thirteen (92%) hypothyroid patients with ulcerative colitis. The median thyroxine dose required by UC patients was 1.54 µg/kg weight/day, that is 26% higher than in the control patients to reach a similar TSH (1.23 µg/kg weight/day; p=0.0002). Since half of our study group consisted of patients aged over 60 years we analyzed the effect of age upon subdivision in two classes. Six out of seven (86%) adult patients required more T4 than the one in the respective control group (1.61 vs 1.27 µg/kg weight/day; +27%; p<0.0001). An increased dose (+17%; p=0.0026) but to a lesser extent, was also required in all patients over 60 years as compared to the control group. Conclusions: In almost all hypothyroid patients with ulcerative colitis, the therapeutic dose of thyroxine is increased. Therefore, ulcerative colitis, even during clinical remission, should be included among the gastrointestinal causes of increased need for oral thyroxine.